Skrining fitokimia dan uji aktivitas antioksidan ekstrak etanol daun mangga kasturi (Mangifera casturi Koesterm.) dari Gampong Drien Bungong, Pidie Jaya dengan metode DPPH - Mulyani, Fitri; Rahayu, Yayuk Putri; Daulay, Anny Sartika; Nasution, Haris Munandar (Journal of Pharmaceutical and Sciences, 2023)
Antioxidants are chemical compounds that, in specific amounts, can inhibit or slow down cell damage caused by free radicals. Antioxidants function to protect the body from free radical attacks. The more free radicals in the body, the more cells will be damaged. One plant that contains antioxidant compounds is casturi mango (Mangifera casturi Koesterm.). Casturi mango (Mangifera casturi Koesterm.) is a plant that contains secondary metabolite compounds such as saponins, tannins, triterpenoids, flavonoids, and phenolics which have potential as antioxidants. This research aimed to determine differences in secondary metabolite compounds and antioxidant activity of ethanol extract of casturi mango leaves (Mangifera casturi Koesterm.) growing in Gampong Drien Bungong, Pidie Jaya. The stages of this research include sample processing, making ethanol extract of kasturi mango leaves, characterization examination, phytochemical screening, and antioxidant activity test. The sample used was musk mango leaves. The ethanol extract of casturi mango leaves (Mangifera casturi Koesterm.) was extracted using maceration with 96% ethanol solvent. The antioxidant activity test was carried out using the DPPH (1-1-Diphenyl-2-Picrylhydrazyl) method using a UV-Vis spectrophotometer at a maximum wavelength of 516 nm and vitamin C as a comparison. Based on the results of phytochemical screening tests, there are differences in secondary metabolites in the ethanol extract of kasturi mango leaves in Gampong Drien Bungong, Pidie Jaya, namely alkaloids, flavonoids, tannins, saponins, steroids, and glycosides, and the results of antioxidant activity obtained an IC50 value of 9.06 ppm with the category very strong, equivalent to the antioxidant potential of vitamin C, having an IC50 value of 4.63 ppm in the robust category.